Performance of physiotherapy in the intensive care unit with an emphasis on the prevention of immobility syndrome: an integrative review (Research, Society and Development, 2020)
Introduction: Immobility Syndrome (SI) is generally considered to be a cluster of systemic changes in individuals who are experiencing prolonged immobility in the ICU. Objective: To investigate the role of physiotherapy in the intensive care unit with an emphasis on the prevention of immobility syndrome. Methodology: This is an integrative review, which searches were carried out for scientific articles in the following databases: MedLine (International Literature in Science and Health), LILACS (Latin American and Caribbean Literature in Science and Health), Cochrane and PubMed. Using the terms as descriptors: Immobility Syndrome; Physiotherapy; Intensive care unit; Early Mobilization; Prevention. Results and Discussions: It was observed that the use of early mobilization protocols is effective in the preventive effect of Immobility Syndrome, avoiding physiological complications that prolonged immobilization causes in the individual. Conclusion: The physiotherapist assists in assisting the vital functions of the various anatomical systems by acting in the prevention and / or treatment of cardiopulmonary, circulatory, muscular and neurological disorders, decreasing the risk of clinical complications and mortality, improving the prognosis of the patient in a serious condition.